Implementation of Project-Based Learning to Improve Student Competence at Vocational High School - Abdillah, Lucky Rafli; Wiyono, Bambang Budi; Sultoni, Sultoni (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
Quality education is essential to create a generation that can compete on a global level. Vocational education, in particular, plays a role in preparing a ready-made workforce. Vocational education in Indonesia still faces challenges, one of which is the inadequate quality of graduates according to the industry. Innovation in learning methods is needed, and project-based learning (PJBL) is considered effective in improving student competence. This study aims to provide an empirical or picture that PJBL can be implemented well and can improve the quality of student competence in every vocational education institution, with a focus on SMK Muhammadiyah 7 Gondanglegi. The location selection is based on information that the institution has successfully implemented the industrial PPA program. This research uses qualitative methodology with case study technique combined with positivistic paradigm. Inductive data analysis was conducted through data reduction, data visualization, conclusion drawing, and verification.The results showed that PJBL at SMK Muhammadiyah 7 Gondanglegi was effective in improving students’ competencies and skills. The implementation of a curriculum that is aligned with industry through cooperation with PT Astra Daihatsu Motor ensures the relevance of education to industry needs. PJBL emphasizes productive education that includes improving hard skills and soft skills, and involves students in real projects that combine theory and practice.